Morphological changes in the section of the Pilica valley between Sulejów and Smardzewice in the years 1968–2016 - Szmidt, Aleksander; Jaskulski, Marcin; Kossowski, Maciej (Acta Geographica Lodziensia, 2024)
The article attempts to determine the geomorphological changes in the bottom of the Pilica valley between Sulejów and Smardzewice near Tomaszów Mazowiecki in the period from the late 1960s to 2016. The research was divided into three parts. The first part included the most faithful reconstruction of the topography of the valley bottom, not only based on a con-tour drawing, but also on an additional geomorphological interpretation not described using classic cartographic methods. In the second stage of work, an attempt was made to recreate the relief of the valley floor, which was already the bottom of an artificial water reservoir. For this purpose, measurements of the reservoir depth were made using sonar. The sonar data were supplemented with the results of geomorphological interpretation and photointerpretation in places where direct measurements could not be made. In the third stage of research, based on the morphometric situation from 1968 and 2016, an attempt was made to determine changes in the morphometry of the valley floor during the formation and functioning of the Sulejów Reservoir.